Balance and coordination training and endurance training after nerve injury. Issue 1 (19th November 2014) - Bonetti, Leandro Viçosa; Schneider, Ana Paula Krauthein; Barbosa, Silvia; Ilha, Jocemar; Faccioni‐Heuser, Maria Cristina
ABSTRACT Introduction: Different rehabilitation treatments have proven useful in accelerating regeneration. Methods: After sciatic nerve crush in rats, we tested balance and coordination training (BCT) and endurance training (ET) through sensorimotor tests and analyzed nerve and muscle morphology. Results: After BCT and ET, rats performed better in sensorimotor tests than did non‐trained animals. However, only BCT maintained sensorimotor function during training. Furthermore, BCT and ET produced significantly larger muscle area than in non‐trained animals. Conclusions: These findings indicate that BCT and ET, when initiated in the early phase after sciatic nerve injury, improve morphological properties of the soleus muscle and sciatic nerve, but only the task‐oriented BCT maintained sensorimotor function. The success of rehabilitative strategies appears to be highly task‐specific, and strategies that stimulate sensory pathways are the most effective in improving balance and/or coordination parameters. Muscle Nerve51: 83–91, 2015